اختلاف العلماء في قاعدة "لا مساغ للاجتهاد في مورد النص" والقول الراجح فيها = The dispute of scholars on the maxim of “ijtihād” is not permitted on the matters that are covered by clear text of sharīʿah” and preferred view - Uddin, Mohammad Burhan; Amanullah, Muhammad; Muhammad, Muhiuddin Khandokar Arif (Selangor Mufti Department (JMNS), 2024)
استهدفت الدراسة اختلاف العلماء في قاعدة "لامساغ للاجتهاد في مورد النص" والقول الراجح فيها، هل تعني هذه القاعدة أن النص والاجتهاد لا يجتمعان كما لا اجتهاد في النصوص القطعية والمحكمات، كأركان الإسلام، والشهادتين، ومسائل العقيدة من توحيد الله تعالى وغيرها؟ هل يمكن التوفيق بينهما؟ فمعناه: إذا امتنع الاجتهاد لمعرفة الحكم مع وجود النص، فهل النص نفسه يجوز فيه الاجتهاد، لا لقبوله أو رفضه، وإنما لفهمه فهما دقيقا؟ ولا يكون ذلك إلا وفق الضوابط التي وضعها الفقهاء لذلك، وهو ما يسمى عند علماء الشريعة "الاجتهاد الاستنباطي"، وهو: فهم آيات الأحكام، وأحاديثها، وتنزيلها على وفق الواقع. وتم عرض أصالة هذه القاعدة من القرآن الكريم، والسنة النبوية، وفي إجماع العلماء، كما تم عرض تطبيقات هذه القاعدة، فهذه القاعدة لو كانت واضحة لدى الفقيه، يمنح له فرصة الاجتهاد ويحضه على استخدام العقل في آي القرآن الكريم والأحاديث النبوية من ناحية. ومن ناحية أخرى إنها تقف جبلا شامخا وسدا منيعا على كل من يتجاوز النصوص القطعية بالاجتهاد أو القياس أو باتباع هواه. وتم توضيح الفرق بين مقولة "لا اجتهاد مع النص وغيرها"، وقاعدة " لا مساغ للاجتهاد في مورد النص"، وسيجري البحث على المنهج الاستقرائي والتحليلي للنصوص وأقوال الفقهاء الواردة فيما يتعلق بالموضوع، ثم دراستها دراسة علمية من ناحية فقهية وأصولية، وينتهي البحث بمعنى القاعدة المختار لدى الباحث بأن "لا مساغ للاجتهاد فيما فيه نص صريح واضح قطعي الدلالة والثبوت." ***** The study aims to clarify the dispute among shariah scholars on the maxim ijtihādis not permitted on the matters that are covered by the text of sharīʿah” and adopt a preferred view. Does this maxim mean that text and ijtihād cannot accumulate? For example, Ijtihād will not be allowed in muḥkamāt, and explicit texts (nuṣuṣqaṭʿiyyah), such as matters related to faith like the oneness of Allah, words of witness, and the pillars of Islam, etc. Can they both be compatible with each other? Meaning that even if ijtihād to derive a rule is impermissible in the presence of a text, it may be permissible in the text itself, not for accepting or rejecting the text, but to get its thorough understanding. And this will be done in accordance with the rules set by scholars. This is what called by the scholars of shariah ‘deductive ijtihād, which means to understand verses and narrations that contain legal rulings and to implement them in reality. The origin of this maxim has been demonstrated from the Holy Quran, the Sunnah of the Holy Prophet, and the consensus of scholars. Similarly, the application of this maxim, the meaning of ijtihād and naṣ, their characteristics, and types of texts whose rulings differ with differences in their status near scholars have also been stated. Hence, this maxim, if becomes completely clear, on the one hand, will give man an opportunity for ijtihād and will urge them to use their intellect in the verses of the Holy Quran and the Hadith, and on the other hand it will prove to be an impregnable wall a tall mountain against whoever tries to surpass the texts with ijtihād and reasoning, or following his desire erroneously advocates the matters that are considered against the explicit texts.